2018
DOI: 10.1063/1.5050117
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant role of taurine and oyster mushroom on kidneys of male mice induced by paraquat herbicide

Abstract: The study aimed to explore potential antioxidant effects of organic taurine and oyster mushroom (Pleurotus ostreatus (Jacq.) P. Kumm) on diets of male mice induced by paraquat herbicide. Thirty male mice were assigned for this study. They were divided into five groups, namely control, oyster mushroom diet, paraquat, paraquat plus oyster mushroom diet, and paraquat plus taurine diet. The concentration of malondialdehyde (MDA), Glutathione, and superoxide dismutase (SOD) was measured, after three weeks animals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
0
0
Order By: Relevance
“…Research showed that giving taurine decreased glucose and total cholesterol levels in mice [7]. Taurine has also been shown to have the ability of antioxidants to prevent oxidative damage to the effects of paraquat induction [8]. Based on the facts above, further research is needed to prove the ability of seagrass as anticancer.…”
Section: Introductionmentioning
confidence: 99%
“…Research showed that giving taurine decreased glucose and total cholesterol levels in mice [7]. Taurine has also been shown to have the ability of antioxidants to prevent oxidative damage to the effects of paraquat induction [8]. Based on the facts above, further research is needed to prove the ability of seagrass as anticancer.…”
Section: Introductionmentioning
confidence: 99%